Creative Control: digital labour, superimposition, datafication, and the image of uncertainty. Issue 4 (2nd October 2017) - Hesselberth, Pepita
ABSTRACT: In this paper I will peruse a specific cinematic example of an uncertain-image, i.e. that of the film Creative Control (Dickinson B, dir. 2015. USA: Ghost Robot | Greencard Pictures | Mathematic | Magnolia Pictures | Amazon Studios). My interest in this film lies not, or at least not per se, or not solely, in its representationalism, but rather in its capturing of various kinds of uncertainty, to which I will here attend by situating the film against the backdrop of three different, yet interrelated, problematics related to the ubiquitous presence of digital imaging technologies: i.e., first, the concerns over digital or immaterial labour and the loss of eros; second, the use of contemporary cinematics (and the superimposition effect in particular) to address these and other issues related to living in 'information-intensive mixed-reality environments;' and third, the film's own suggestive counter-image, which is that of the characters' partly defection, and, arguably, that of the image's own withdrawal from the world.